The impact of alternatives to corporal punishment on the culture of teaching and learning at the Lepato High School in the Limpopo Province - Malatji, Thabo Hermanus (University of Limpopo, 2006)
The purpose of this study was to determine the impact that alternatives to corporal punishment had on the culture of teaching and learning at Lepato High School in the Limpopo Province. The methods used for data collection involved the use of questionnaires, personal interviews and participation observation. The findings indicated that implementing alternatives to corporal punishment without proper support from all stakeholders in education was disastrous for this school. This study further revealed that parental involvement in education is necessary for the successful application of alternatives to corporal punishment in schools. The study findings will make a positive contribution to the improvement of the handling of disciplinary problems in various schools especially in the Limpopo Province and South Africa in general.
Thesis (M.Dev.) --University of Limpopo, 2006.
Keywords: Corporal punishment; Teaching and learning; 371.5420968; School discipline; Teacher-student relationships